2018
DOI: 10.5194/bg-15-1895-2018
|View full text |Cite
|
Sign up to set email alerts
|

Biological production in the Indian Ocean upwelling zones –Part 1: refined estimation via the use of a variable compensation depth in ocean carbon models

Abstract: Abstract. Biological modelling approach adopted by the Ocean Carbon-Cycle Model Intercomparison Project (OCMIP-II) provided amazingly simple but surprisingly accurate rendition of the annual mean carbon cycle for the global ocean. Nonetheless, OCMIP models are known to have seasonal biases which are typically attributed to their bulk parameterisation of compensation depth. Utilising the criteria of surface Chl a-based attenuation of solar radiation and the minimum solar radiation required for production, we ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 95 publications
(135 reference statements)
1
35
0
Order By: Relevance
“…Their focus on the marine resource reflected the abundance of fish in coastal waters due to seasonal upwelling (e.g. Disspain et al, : 429; Standen et al, : 163), a mechanism that also causes an abundance of fish stocks off the coast of Oman (Cleuziou & Tosi, : 14; Sreeush et al, ). Similarly, Aboriginal groups in the western desert of Australia are known to utilise different environmental zones in the landscape, including river fish and wild game, on a seasonal basis (Cane, ).…”
Section: Discussionmentioning
confidence: 99%
“…Their focus on the marine resource reflected the abundance of fish in coastal waters due to seasonal upwelling (e.g. Disspain et al, : 429; Standen et al, : 163), a mechanism that also causes an abundance of fish stocks off the coast of Oman (Cleuziou & Tosi, : 14; Sreeush et al, ). Similarly, Aboriginal groups in the western desert of Australia are known to utilise different environmental zones in the landscape, including river fish and wild game, on a seasonal basis (Cane, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they were found notably lower than NH3 and even SH3, around the bomb peak period (1964( -1967. A potential influencing factor to be addressed might be the close proximity to the coast of the Arabian Sea, where upwelling of nutrient and carbon rich waters causes an outgassing of 'older' CO2 into the atmosphere (Takahashi et al, 2009;Sreeush et al, 2018) that dilutes the bomb peak signal. But this dilution effect should also be seen in pre-bomb peak F 14 C data.…”
Section: F 14 C Values In Baobab Wood Are Very Likely Altered By Carbmentioning
confidence: 99%
“…Fluctuations in the vertical mixing process also influences the overall time span of light experienced by the phytoplankton (McCreary et al, 1996) in the water column. Moreover, the variability in bio-physical processes in SWTIO region are mostly controlled by the strength and duration of the monsoon winds and associated nutrient dynamics, and the downward trend in biological production, if any, in these upwelling systems has immense ramification on the marine foodweb and economic status of the fishing community of this region (Roxy et al, 2016;Sreeush et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Resplandy et al (2009) have shown that interannual variability of the thermocline and its role modulating the response to Madden-Julian Oscillation (MJO) controls the chlorophyll-a and export flux of carbon. Further, recent study has shown that Ocean Carbon-Cycle Model Intercomparison Project (OCMIP-II)based estimated CO 2 flux and pCO 2 underestimated the SCTR variability portraying it as a CO 2 sink region (Sreeush et al, 2018). Studies carried out in the SCTR region either describe the role of physical forcings in modulating the phytoplankton biomass (chlorophyll-a) concentrations (George et al, 2013;Roxy et al, 2016;Dilmahamod et al, 2016) and/or satellite or model-based PP (Resplandy et al, 2009;Sreeush et al, 2018); however, none of the studies have reported any in situ measured phytoplankton C-uptake rates (PP), phytoplankton size class/community, and phytoplankton physiological perspective vis-à-vis the physical forcings prevailing in this oligotrophic region.…”
Section: Introductionmentioning
confidence: 99%